Impact of interprofessional education module on attitudes of health-care providers involved in maxillofacial rehabilitation: A cross-sectional study - Saee Deshpande; Usha Radke (Wolters Kluwer Medknow Publications, 2017)
Purpose: Rehabilitation of maxillofacial deformities is a challenging task because it involves not only a lot of skills and expertise but also many disciplines working in unison for optimum outcome. However, more often than not a prosthodontist is not a member of tumor board and consulted after surgery which affects the prognosis of the rehabilitation adversely. There was a perceived need to create awareness among referring surgeons and physicians, and interprofessional education (IPE) initiatives were deemed necessary to improve this collaboration. Methodology: Four-hour IPE module was developed involving residents and faculty from three disciplines. The change in attitudes was evaluated quantitatively using Attitudes toward Health Care Teams questionnaire both before and after the module. Semi-structured interviews with selected participants provided the qualitative feedback. Results: The questionnaire consisted of 14 questions answered on 5-point Likert scale (1-5). The mean score of pretest was 44.2 and of posttest was 49.1. Difference was statistically significant (P < 0.05). Higher score indicates better attitude. Conclusion: A brief IPE program can improve interprofessional attitudes and collaborative behavior of health-care professionals involved in maxillofacial rehabilitation. It enables the professionals to understand interact and share viewpoints regarding most critical issues faced by them and find solutions to achieve best possible patient care.